The coolie speaks : Chinese indentured laborers and African slaves in Cuba - Yun, Lisa, 1963- (Asian American history and culture., 2008)
The Coolie Speaks focuses on Chinese laborers who worked side by side with African slaves in Cuba and wrote of their experiences of new bondage. Examining these narratives of resistance, the book reconceptualizes diasporic representations and histories to offer transformative re-examinations of "Chinese," "African," and "Latino" in mutually imbricated contexts